[INVITED] Coupling of polarisation of high frequency electric field and electronic heat conduction in laser created plasma. (August 2016) - Gamaly, Eugene G.; Rode, Andrei V.
Abstract: Powerful short laser pulse focused on a surface swiftly transforms the solid into the thermally and electrically inhomogeneous conductive plasma with the large temperature and dielectric permeability gradients across the focal spot. The laser-affected spot becomes thermally inhomogeneous with where temperature has maximum in the centre and gradually decreasing to the boundaries of the spot in accord to the spatial intensity distribution of the Gaussian pulse. Here we study the influence of laser polarisation on ionization and absorption of laser radiation in the focal spot. In this paper we would like to discuss new effect in thermally inhomogeneous plasma under the action of imposed high frequency electric field. We demonstrate that high-frequency (HF) electric field is coupled with the temperature gradient generating the additional contribution to the conventional electronic heat flow. The additional heat flow strongly depends on the polarisation of the external field. It appears that effect has maximum when the imposed electric field is collinear to the thermal gradient directed along the radius of a circular focal spot. Therefore, the linear polarised field converts the circular laser affected spot into an oval with the larger oval's axis parallel to the field direction. We compare the developed theory to the available experiments, discuss the results and future directions.